Analisis Harga Saham Syariah di Indonesia: Ketidakpastian Kebijakan, Harga Minyak Dunia dan Harga Emas - Jerry Setiawan; Alpon Satrianto (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2021)
This study aims to determine the effect of US Economic Policy Uncertainty, Singapore Economic Policy Uncertainty, Oil Price, and Gold Price on the Shariah Stock Price in Indonesia. The data used are secondary monthly time series data from 2009M1 to 2019M12 which is obtained from related website. This study used multiple linear regression analyis model with the OLS (Ordinary Least Square) method to determine how the influence of the independent variable on the dependent variable. The results of this study incicated that simultaneously, US Economic Policy Uncertainty, Singapore Economic Policy Uncertainty, Oil Price, and Gold Price have a significant influence on the Shariah Stock Price in Indonesia. Furthermore, partialy: (1) US Economic Policy Uncertainty has a negative and significant effect on the Shariah Stock Price in Indonesia; (2) Singapore Economic Policy Uncertainty has a positive and insignificant effect on the Shariah Stock Price in Indonesia; (3) the oil price has a negative and significant effect on the Shariah Stock Price in Indonesia; (4) the gold price has a positive and significant effect on the Shariah Stock Price in Indonesia.